(untitled) (Asian-Australasian Journal of Food Safety and Security, 2021)
Antibiotic residues remain in edible portion of meat animals that have been treated with antibiotics. The aim of this study was to detect enrofloxacin residue after discriminate and indiscriminate administration and investigate the effect of enrofloxacin in growth of poultry. 18 broilers DOC (Cobb-500) were collected & reared up to 31 days. On day 16, they were randomly divided into 3 groups, namely Group–A (Control group), Group-B (Discriminate group) and Group-C (Indiscriminate group). Each group contains 6 birds. The discriminate and indiscriminate groups were treated with antibiotic, enrofloxacin. In Group-B withdrawal period was followed and treatment was stopped before 7 days of sacrifice. On the other hand, withdrawal period was not maintained in indiscriminate group and antibiotic treatment was continued until the day of sacrifice. Body weight was recorded daily in the morning. On 31st day mean body weight was highest in Group-C (1901.17 ± 15.22gm) and lowest body weight was in Group-A (1453.33 ± 26.39gm). The differences among mean weight gain were statistically significant (P<0.005) in both discriminate & indiscriminate group compared to control group. Test results found in TLC showed that in discriminate antibiotic group (Group-B) 50% liver samples, 33.33% kidney and 16.67% fat samples were enrofloxacin positive. No sample of thigh muscle, breast muscle and spleen was positive. In indiscriminate antibiotic group (group-C) all the samples were positive in case of liver, kidney, fat and spleen samples. Only 33.33% and 16.67 % samples were positive in case of fat and thigh muscle samples. All the samples of control group (Group-A) were negative. Overall, the present study documented the widespread abuse of enrofloxacin and failure to implement the recommended withdrawal period will undeniably leads to deposition of residues in broiler tissues. Asian Australas. J. Food Saf. Secur. 2021, 5 (1), 11-18